Cover Vol. 17 No. 02 Desember 2020 - PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal Of Indonesia) (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2020)
Cover Vol. 17 No. 02 Desember 2020